'A Great Turkish Policy': Winston Churchill, the Ottoman Empire and the Origins of the Dardanelles Campaign. Issue 349 (January 2017) - DOCKTER, A. WARREN
Abstract: One of the most important players in British/Ottoman relations and the ultimate breakdown of those relations during the Edwardian period and war years was Winston Churchill. Diplomatic historians and Churchill biographers have focused on Churchill's role in the attempted naval conquest of the Dardanelles, the unsuccessful Gallipoli campaign and Churchill's wartime disdain for the Ottomans. In doing so, they tend to portray Churchill's relationship with the Ottoman empire in a negative light, assuming that he, like much of the war cabinet, based his strategies and diplomacy on ideas of European superiority and oriental weakness. However, new archival evidence has come to light which paints a much more nuanced account of Churchill's role in British/Ottoman diplomacy. Using these new sources such as Churchill's personal correspondence with Ottoman leaders such as Djavid Bey and Enver Pasha, this article will explore Churchill's relationship with the Ottoman empire and his role in shaping British/Ottoman diplomacy. Taking into account the history of Churchill's opinions, attitudes and policies, this article will reveal that Churchill was initially supportive of an Anglo‐Ottoman alliance, only to be thwarted by the First World War. It will demonstrate that Churchill's support for an Ottoman alliance owed partially to his Victorian Tory background and to a greater extent, a fear of a pan‐Islamic uprising. Ultimately this article will reveal that Churchill's relationship with the Ottoman empire was far more complex than is typically thought and was built on a unique blend of Victorian orientalism, geopolitical strategy and personal sympathies.